Kenyamanan Termal Terhadap Desain Arsitektur Berkelanjutan Pada Masjid Raya Alh-Azhar Summarecon Bandung - Eliani, Imas; Maulana Subki, Raksa; Astrid Hartoety, Dianna; Badar Tubanie, Moch. Riou (Jurnal Syntax Fusion, 2025)
This study aims to analyze the level of thermal comfort in the context of sustainable architectural design, with a case study focusing on Al-Azhar Grand Mosque Summarecon Bandung. The research employs both quantitative and qualitative approaches, including temperature and humidity measurements, field observations, and documentation. The findings indicate that the application of sustainable architectural principles, such as the use of natural ventilation, natural lighting, and environmentally friendly materials, plays a significant role in enhancing thermal comfort. The recorded average temperature in the mosque ranges from 24.38°C to 31.68°C, while humidity levels vary between 56% and 91%. Although thermal comfort is generally achieved, challenges remain in addressing high humidity levels and temperature imbalances at certain times. Therefore, this study recommends optimizing the ventilation system and selecting materials with moisture-absorbing properties to further enhance the comfort of mosque users.